Mineralisation of natural rubber (poly cis 1-4 isoprene) by co-cultured bacterial strains isolated from rubber plantation area - Muralidharan, Manasa; Krishnaswamy, Veena Gayathri (International Journal of Biological Research, 2016)
Objective: To isolate Natural Rubber degrading Bacterial co-cultures from rubber plantation soil and to characterize and identify the organisms by 16s r RNA sequencing.Methods: Cocultures of the bacteria were isolated from the contaminated site by enrichment culture technique. Plate assay method and liquid assay method by using Mineral Salt Medium was followed for screening of bacteria for its capacity to mineralize Natural rubber. Degradation was confirmed by Spectrophotmetric and Fourier Transform Infra-Red (FTIR) studies.Natural rubber degraded by the cocultures were studied at different concentrations and the physico-chemical analysis were optimized (pH, temperature, carbon and nitrogen sources)Results: Isolated organism was identified as Bacillus cohnii and Brevundimonas naejangsanensis. The co-cultures were able to utilize the Natural rubber which was confirmed by Spectrophotometric and FTIR studies. From the current study it was evaluated that Natural rubber was mineralized up to 50 % where optimum concentration was 10 %.Conclusion: From current investigation, it can be concluded that our isolated bacterial cocultures Bacillus cohnii and Brevundimonas naejangsanensis have the capacity to mineralize Natural rubber and hence such isolated cocultures can be used in removal of from waste Natural rubber products in the environment.